On Corporate Virtue - Gowri, Aditi (Journal of business ethics, 2007)
This paper considers the question of virtues appropriate to a corporate actor’s moral character. A model of corporate appetites is developed by analogy with animal appetites; and the pursuit of initially virtuous corporate tendencies to an extreme degree is shown to be morally perilous. The author thus refutes a previous argument which suggested that (1) corporate virtues, unlike human virtues, need not be located on an Aristotelian mean between opposite undesirable extremes because (2) corporations do not have appetites; and (3) corporate virtues must serve the end of sustainable profit. If these disanalogies between corporate and human virtue no longer hold, then the stage is set for us to formulate a more adequate model of good corporate character that would encompass other-regarding virtues.